Granulomatous gastritis in Wegener's disease: differentiation from Crohn's disease supported by a positive test for antineutrophil antibodies. Issue 4 (April 1997) - Temmesfeld-Wollbrueck, B; Heinrichs, C; Szalay, A; Seeger, W
Abstract : BACKGROUND: This report concerns the gastric manifestation of Wegener's granulomatosis in a 44 year old white female patient who initially presented with abdominal pain, vomiting, and iridocyclitis. FINDINGS: The clinical findings and the histopathological proof of granulomatous gastritis in the absence of necrotising vasculitis were initially considered to be indicative of a diagnosis of Crohn's disease showing isolated gastric involvement. A five month course of steroids resulted in temporary relief; thereafter the patient developed severe rhinitis with mucosal ulcerations. At this point biopsy of nasal mucosa disclosed the classic histopathological signs of Wegener's granulomatosis. A positive test for antineutrophil cytoplasmic antibodies (ANCAs) with a cytoplasmic pattern (c-ANCA) and antigenic specificity for proteinase 3 (PR-3) were found. The patient is in complete remission one year after diagnosis and treatment with steroids and cyclophosphamide. CONCLUSIONS: Wegener's granulomatosis can also involve the gastrointestinal tract. Granulomatous inflammation of the stomach, although a rare finding and non-specific, should include Wegener's disease in the differential diagnosis. The histological proof of necrotising vasculitis is dependent on the depth of the biopsy and therefore can be easily missed. Differential diagnosis can be clarified by ANCA testing.